ChemInform Abstract: Visible‐Light‐Assisted Selective Catalytic Reduction of Nitric Oxide with Ammonia over Dye‐Modified Titania Photocatalysts. Issue 35 (September 2015) - Yamamoto, Akira; Teramura, Kentaro; Hosokawa, Saburo; Shishido, Tetsuya; Tanaka, Tsunehiro
Abstract Dye‐modified TiO2 photocatalysts show a high photocatalytic activity for the selective catalytic reduction of NO with NH3 in the presence of O2 under visible‐light irradiation.